'Grip and Drop' Physical Education to Promote Independent Participation for Children with Low-Incidence Disabilities. (3rd September 2018) - Jagodzinski, Lily; Kozub, Francis M.
Abstract : This article provides a useful activity for adapted physical educators to use when programming for students with low-incidence disabilities. The goal of the activity is to promote movement that is fun and builds upon skills needed for independence. With the help of a task analysis, the game "grip and drop" can help children develop grasping, releasing, reaching and midline crossing skills. These skills are necessary for children with low-incidence disabilities to succeed in tasks of daily living. Additionally, modifications and lesson extensions are provided for the development of a unit plan for learners served in either integrated or more restrictive settings.